Deactivation and Regeneration of Oxygen Reduction Reactivity on Double Perovskite Ba(2)Bi(0.1)Sc(0.2)Co(1.7)O(6-x) Cathode for Intermediate-Temperature Solid Oxide Fuel Cells - Zhou, W.; Sunarso, J.; Motuzas, J.; Liang, F.; Chen, Z.; Ge, L.; Liu, Shaomin; Julbe, A.; Zhu, Z. (American Chemical Society, 2011)
In situ high-temperature X-ray diffraction and thermal gravimetric−differential thermal analysis on room-temperature powder, as well as X-ray diffraction, Raman spectroscopy, and transmission electron microscopy on quenched powder, were applied to study crystal structure and phase transformations in Ba2Bi0.1Sc0.2Co1.7O6−x (BBSC). Heating BBSC in air to over 800 °C produces a pure cubic phase with space group Fm3m (no. 225), and cooling down below 800 °C leads to a mixture of three noncubic phases including an unknown phase between 200 and 650 °C, a 2H hexagonal BaCoO3 with space group P63/mmc (no. 194) between 600 and 800 °C, and an intermediate phase at 800 °C. These three phases exist concurrently with the major cubic phase. The weight gain and loss between 300 and 900 °C suggest the occurrence of cobalt reduction, oxidation, and disproportion reactions with dominant reduction reaction at above 600 °C. The thermal expansion of BBSC was also examined by dilatometry. BBSC has a highly temperature-dependent thermal expansion coefficient which relates well with its structure evolution. Furthermore, the oxygen reduction reaction (ORR) of BBSC was probed by symmetrical cell and three-electrode configurations. The presence of hexagonal phase at 700 °C rarely affects the ORR performance of BBSC as evidenced by a slight increase of its area-specific resistance (ASR) value following 48 h of testing in this three-electrode configuration.This observation is in contrast to the commonly held point of view that noncubic phase deteriorates performance of perovskite compounds (especially in oxygen transport applications). Moreover, cathodic polarization treatment, for example, current discharge from BBSC (tested in three-electrode configuration), can be utilized to recover the original ORR performance. The cubic structure seems to be retained on the cathodic polarization—the normal cathode operating mode in fuel cells. Stable 72-h performance of BBSC in cathodic polarization mode further confirms that despite the presence of phase impurities, BBSC still demonstrates good performance between 500 and 700 °C, the desired intermediate operating temperature in solid oxide fuel cells.